2001
DOI: 10.1093/humrep/16.7.1512
|View full text |Cite
|
Sign up to set email alerts
|

The seasonality of live birth is strongly influenced by socio-demographic factors

Abstract: The number of births varies markedly by season, but the causes of this variation are not well understood. The proposed explanations include temperature or photoperiod (affecting hormonal concentrations, sperm quality or sexual activity), seasonal variation in pregnancy loss, or cultural factors. In this paper we examined whether birth seasonality is influenced by socio-demographic factors. We used data on all live births registered in the Czech Republic in 1989-1991 (n = 387 496). Differences in the degree of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
91
2
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(103 citation statements)
references
References 21 publications
6
91
2
1
Order By: Relevance
“…Most births have been observed between March and May in Northern Europe, and this rate has been shown to declines between October and November. In contrast, the birth rate increased between July and September and decreased from March to May in the United States of America (16). A study by Basso et al (17) concluded that summer was the most preferred season for pregnancy in Denmark, Italy and Spain.…”
Section: Discussionmentioning
confidence: 98%
“…Most births have been observed between March and May in Northern Europe, and this rate has been shown to declines between October and November. In contrast, the birth rate increased between July and September and decreased from March to May in the United States of America (16). A study by Basso et al (17) concluded that summer was the most preferred season for pregnancy in Denmark, Italy and Spain.…”
Section: Discussionmentioning
confidence: 98%
“…In a recent paper, Buckles and Hungerman (2010) …nd that babies born in the winter are more likely to have mothers who are unmarried, who are teenagers or who lack a high school diploma. Bobak & Gjonca (2001) …nd that the magnitude of seasonal variation in births was particularly strongly associated with maternal socio-demographic characteristics.…”
Section: School Entrance Age and Intertemporal Maternal Labor Supply:mentioning
confidence: 98%
“…Data from the NCES suggests that in 1980, 30% of kindergartners between the ages of 4 to 6 attended full day kindergarten. 10 However, many half-day kindergartens had inexpensive extended day programs attached to them. So the estimated elasticities could be up to twice the true numbers but more plausibly is somewhere in between.…”
Section: ' Back-of-the-envelope'elasticity Estimatesmentioning
confidence: 99%
“…All but one (Landgren et al, 1996) reported significant associations with preterm delivery. Three of the studies describing significant associations considered the relationship linear, and reported a increased risk for preterm birth ranging from 3.5% (Bobak et al, 2001;Sagiv et al, 2005) in the Czech Republic and Pennsylvania to 6.4% in Vancouver (Liu et al, 2003) for a 10 μg/m 3 increase in SO 2 levels. The Xu et al study (1995) in Beijing, China examined a log linear relationship and found a 21% increase in the risk of preterm delivery for each ln μg/m 3 increase in SO 2 levels.…”
Section: Prematuritymentioning
confidence: 99%